Effect of Additives on Characterization and Photocatalytic Activity of Tio𝟐/ZnO Nanocomposite Prepared via Sol-Gel Process - Shahram Moradi; Parviz Aberoomand Azar; Sanaz Raeis Farshid; Saeed Abedini Khorrami; Mohammad Hadi Givianrad (International Journal of Chemical Engineering)
TiO2/ZnO nanocomposites were prepared by the sol-gel method with and without addatives such as carboxy methyl cellulose (CMC), poly(ethylene glycol) (PEG), polyvinylpyrrolidon, (PVP), and hydroxylpropylcellulose (HPC). The characteristics of the prepared TiO2/ZnO nanocomposites were identified by IR spectra, X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS) methods. The additives have a significant effect on the particle size distribution and photocatalytic activity of TiO2/ZnO nanocomposites. The photocatalytic activity of the synthesized nanocomposites was investigated for decolorization of methyl orange (MO) in water under UV-irradiation in a batch reactor and the results showed that the photocatalytic activity of the nanocomposites have been increased by CMC, PEG, PVP, and HPC, respectively. SEM has shown that the particle size distribution of TiO2/ZnO nanocomposite in the presence of HPC was better than the other samples.